2014
DOI: 10.14444/1018
|View full text |Cite
|
Sign up to set email alerts
|

Annulo-nucleoplasty using Disc-FX in the management of lumbar disc pathology: Early results

Abstract: BackgroundBack pain due to Lumbar Disc Disease is a major clinical problem. The treatment options range from physiotherapy to fusion surgery. A number of minimally invasive procedures have also been developed in the recent past for its management. Disc-FX is a new minimally invasive technique that combines percutaneous discectomy, nuclear ablation and annular modification. Literature on its role in the management of lumbar disc pathology is scarce.MethodsWe included 24 consecutive patients who underwent the Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…Results of another study indicated that although improvement seen in the degenerative disc disease was not significantly different from that of the contained lumbar disc herniation subgroup, the contained group required re-intervention within 1 year of the procedure [10].…”
Section: Nrs (N=43) Mean ± Sd P Valuementioning
confidence: 89%
See 3 more Smart Citations
“…Results of another study indicated that although improvement seen in the degenerative disc disease was not significantly different from that of the contained lumbar disc herniation subgroup, the contained group required re-intervention within 1 year of the procedure [10].…”
Section: Nrs (N=43) Mean ± Sd P Valuementioning
confidence: 89%
“…The patients with a focal disc prolapse may have had a preexisting thinning of the annulus fibrosus; creation of a 2.7-mm annulotomy near the weakened area may have predisposed them to recurrent disc prolapse [10]. Carragee et al [15] studied clinical outcomes after lumbar discectomy for treatment of sciatica and demonstrated that patients with lumbar disc herniation's containing no fragments experienced poorer treatment outcomes than did those with other types of herniation's, with 38% having recurrent or persistent sciatica.…”
Section: Nrs (N=43) Mean ± Sd P Valuementioning
confidence: 99%
See 2 more Smart Citations
“…5 The effectiveness of both LS and RF has been reported in several studies, with improvement rates of above 70%. 7,8,11,[13][14][15][16][17][18][19][20][21] Nevertheless, their safety margin and degree of complications continue to create extensive controversies between different surgeons. The purpose of the study was to report and compare the number and grade of major complications present in non-endoscopic thermal discectomy and nucleoplasty, in the treatment of discogenic axial lumbar pain using LS and RF technologies.…”
Section: Introductionmentioning
confidence: 99%